It is classroomed by poetry, what such a literary experience as a poetry slam? - Vieira Santos Ribeiro, Joao Ricardo; Mello Miranda, Katia Rodrigues [UNESP] (Univ Fed Fluminense, Dept Historia, 2020)
The importance of poetry for the development of being and society is a consensus in the educational environment; however, research certifies the little expressiveness of its teaching for the literary formation of students. In view of this observation, and without denying the value of the canon or echoing an already recurring discussion about it, our objective is, in general, to reflect on the corpus of lyrical productions selected by the school, which we agree needs to be expanded. For this, as an alternative to meaningful work with poetry in the classroom, we present Poetry Slam, which in recent years has been gaining space in the sphere of oral literary manifestations, through its so-called battles of spoken poetry, in which the authors they decree in a performative way their texts, in the time of three minutes, without the use of scenic resources. Considering the feasibility of teaching slam, from the perspective of literary literacy, we propose a basic sequence, elaborated based on the assumptions of Cosson (2014) and capable of application in high school, which, among other possibilities, results in the fight against racism and empowerment individual students.
Keywords: Poetry Slam; Teaching of Poetry; Teaching proposal